Indirect model predictive control strategies with input filter resonance mitigation for a matrix converter operating at fixed switching frequency - Rivera, Marco; Nikolic, A.; Tarisciotti, Luca; Wheeler, Patrick (2017)
The main issues of the implementation of model predictive control in a direct matrix converter are the high com¬putational cost, the adequate selection of weighting factors and the variable switching frequency which could produce resonances in the input filter. In order to solve these problems, in this paper are proposed two indirect model predictive control techniques with input filter resonance mitigation operating at fixed switching frequency. The method is based on the fictitious dc-link concept, which has been used in the past for the classical modulation and control techniques of the direct matrix converter. Simulated results confirm the feasibility of the proposal demonstrating that it is an alternative to classical predictive control strategies for the direct matrix converter.